2018
DOI: 10.1194/jlr.m083832
|View full text |Cite
|
Sign up to set email alerts
|

Impaired thermogenesis and sharp increases in plasma triglyceride levels in GPIHBP1-deficient mice during cold exposure

Abstract: Glycosylphosphatidylinositol-anchored high density lipoprotein–binding protein 1 (GPIHBP1), an endothelial cell protein, binds LPL in the subendothelial spaces and transports it to the capillary lumen. In Gpihbp1−/− mice, LPL remains stranded in the subendothelial spaces, causing hypertriglyceridemia, but how Gpihbp1−/− mice respond to metabolic stress (e.g., cold exposure) has never been studied. In wild-type mice, cold exposure increases LPL-mediated processing of triglyceride-rich lipoproteins (TRLs) in bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
3
11
0
Order By: Relevance
“…However, the whole lipoprotein uptake in Angptl4 / Gpihbp1 / mice was not any greater than that observed in Gpihbp1 / mice. This result is consistent with the recent report from Larsson et al (32), who also found that at room temperature, TG uptake, but not lipoprotein particle uptake (as measured by uptake of radiolabeled retinol), was increased in the BAT of Angptl4 / Gpihbp1 / mice compared with Gpihbp1 / mice. Although there was no increase in whole lipoprotein uptake, the already substantial uptake in Angptl4 / Gpihbp1 / mice may explain the improved TG Fig.…”
Section: Localization In Gpihbp1supporting
confidence: 93%
See 2 more Smart Citations
“…However, the whole lipoprotein uptake in Angptl4 / Gpihbp1 / mice was not any greater than that observed in Gpihbp1 / mice. This result is consistent with the recent report from Larsson et al (32), who also found that at room temperature, TG uptake, but not lipoprotein particle uptake (as measured by uptake of radiolabeled retinol), was increased in the BAT of Angptl4 / Gpihbp1 / mice compared with Gpihbp1 / mice. Although there was no increase in whole lipoprotein uptake, the already substantial uptake in Angptl4 / Gpihbp1 / mice may explain the improved TG Fig.…”
Section: Localization In Gpihbp1supporting
confidence: 93%
“…Indeed, Dijk et al (31) proposed that an alternative ANGPTL4-sensitive pathway might allow transport of LPL in the absence of GPIHBP1 and ANGPTL4. In support of this idea, using immunofluorescence, a study by Larsson et al (32) found some evidence of LPL on the vascular lumen of capillaries in Angptl4 / Gpihbp1 / mice. In contrast, we found no evidence of increased LPL entry into the vasculature.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…These processes ensure the energy supply to maintain the physiological functions of the body. On the contrary, fasting caused up-regulation of ANGPTL4 in WAT [21,39]. The up-regulated ANGPTL4 reduces the uptake of circulating triglycerides by WAT through reducing LPL activity.…”
Section: Starvation Statusmentioning
confidence: 95%
“…Under starvation, the expression of ANGPTL8 decreased by nearly 70% in WAT [21], and the expression of ANGPTL8 in BAT and liver was also significantly reduced [39]. Under starvation, circulating ANGPTL8/ANGPTL3 complex reduces [10], which increases LPL activity in peripheral tissues and in turns increases the uptake of VLDL by skeletal muscles and the heart.…”
Section: Starvation Statusmentioning
confidence: 99%